Nonlinear dynamics of heart rate during slow breathing exercise - Porto, Andrey A.; Tavares, Bruna S. [UNESP]; Vidigal, Giovanna [UNESP]; Garner, David M.; Raimundo, Rodrigo D.; de Abreu, Luiz Carlos; Bocalini, Danilo; Valenti, Vitor E. [UNESP] (My University, 2018)
The acute effects of slow breathing exercises on the complex behaviour of heart rate regulation were investigated. We evaluated 21 healthy male volunteers aged between 18 and 30 years old. Heart rate variability was investigated 10 minutes during spontaneous breathing and five minutes during slower breathing exercises (6 cycles/min). The consequent nonlinear metrics of heart rate variability were applied: Symbolic analysis, Shannon Entropy, Rényi Entropy, Tsallis Entropy, Approximate Entropy, Sample Entropy and Detrended Fluctuation Analysis. The symbolic exhibited an increase in two like variation and decrease in two unlike variation. Detrended Fluctuation Analysis was significantly higher during slow breathing exercises (0.6454±0.201 vs. 0.3949±0.205; p=0.0003). Approximate entropy was significantly lower during slow breathing exercises (0.8620±0.121 vs. 0.7677±0.134; p=0.0221). No significant changes were detected for Shannon Entropy, Rényi Entropy, Tsallis Entropy and Sample Entropy. In conclusion, slow breathing exercises decrease nonlinear behaviour of heart rate dynamics in healthy young males followed by reduced vagal control of heart rate dynamics. We propose that the linear behaviour of respiratory patterns influences the complexity of HRV.